Advanced structural inorganic chemistry - Li, Wai-Kee.; Zhou, Gong-du, 1931-; Mak, Thomas C. W., 1936- (Oxford : Oxford University Press, 2008)
An English edition of a textbook based on teaching at the final year undergraduate and graduate level. It presents structure and bonding, generalizations of structural trends, crystallographic data, as well as highlights from the recent literature.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Chemistry, Inorganic; Chemistry, Physical and theoretical